Withdrawal of U.S. Military Engagement and The Erosion of Liberal Democratization: An Afghan Perspective - Subrat K. Ratha (Mengeja Indonesia Publisher, 2022)
The recent humanitarian catastrophe in Afghanistan denotes the failure of US-led liberal democratization in authoritarian and non-democratic countries, especially in the Muslim world. Having been witnessed a long-term war in a foreign land, after a detailed deliberation in the Doha agreement, the U.S. military stand-up has been overthrown with the rise of the Taliban. It can be viewed as a failed policy of the U.S. government since the emergence of the